Neoadjuvant chemoradiation is associated with improved overall survival in older patients with esophageal cancer. Issue 1 (January 2018) - Guttmann, David M.; Mitra, Nandita; Metz, James M.; Plastaras, John; Feng, Weiwei; Swisher-McClure, Samuel
Abstract: Objectives: The aim of this study was to characterize outcomes associated with neoadjuvant chemoradiation prior to esophagectomy, compared to esophagectomy alone, in older patients with esophageal cancer. Materials and Methods: We conducted an observational cohort study in patients ≥ 70 years with locally-advanced esophageal cancer undergoing esophagectomy ± neoadjuvant chemoradiation between 2006 and 2012 using the National Cancer Database. A Cox proportional hazards model with inverse probability of treatment weighting (IPTW) using the propensity score was developed to assess the association between trimodality therapy and overall survival. Perioperative complications and pathologic outcomes associated with trimodality therapy were identified with multivariable logistic regression. Results: 1364 patients were included; the mean age was 75 (range 70–90). 904 (66%) were treated with trimodality therapy and 460 (34%) were treated with esophagectomy alone. On IPTW Cox analysis, neoadjuvant chemoradiation was associated with improved overall survival (HR = 0.76, 95%CI [0.70–0.82], p  ≤ 0.001). Further, trimodality therapy was associated with lower rates of margin-positive resection (5% vs. 18%; OR = 0.26, 95%CI [0.18–0.37], p  < 0.001) and in 18% of trimodality patients, there was no detectable tumor at surgery. 90-day mortality rates were not statistically different (14% vs. 12%; OR = 0.99, 95%CI [0.73–1.36], p  = 0.22). Neoadjuvant chemoradiation was associated with lower 30-day readmission rates (5% vs. 8%; OR = 0.48, 95%CI [0.31–0.73], p  = 0.004) and shorter surgical hospital stay (median 10 vs. 12 days, p  < 0.001) compared to esophagectomy alone. Conclusion: In older patients with esophageal cancer, trimodality therapy, compared to esophagectomy alone, is associated with improved overall survival and favorable pathologic and perioperative outcomes. Further studies are needed to identify which older patients are most suitable for trimodality therapy.